DEKONSTRUKSI DEFINISI AKUNTANSI DALAM PERSPEKTIF PANCASILA - Sitorus, Jordan Hotman Ekklesia; Triyuwono, Iwan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The purpose of this research is to create a new definition of accounting based on Pancasila values. The author uses a qualitative method which relies on the postmodernism method in the point of view of Pancasila to make a new definition. The result of this research is a new accounting definition based on each sila and the result is being formulated into a new definition. The accounting definition in Pancasila perspective is the human accountability to God by humanizing the human, spirit of brotherhood, uplifting the degree of society, and balancing the physical and spiritual needs of human in financial activity. Keywords:Â Â Â Accounting Definition, Pancasila, Posmodernism, Culture, Society, Financial Activity.